KERAGAMAN VEGETASI GULMA DI BAWAH TEGAKAN POHON KARET ( Hevea brasiliensis ) PADA UMUR DAN ARAH LERENG YANG BERBEDA DI PTPN IX BANYUMAS - Bhaskara Anggarda Gathot Subroto; Bayu Aji Setiawan (Universitas Lancang Kuning, 2018)
This research was conducted in PTPN IX Afdeling Krumput Banyumas in July 2016, with observational survey method is by field orientation, exploration, and analysis of vegetation. The data collection is done by means of interviews and direct observation. Preliminary surveys conducted to seek information from relevant agencies, environmental conditions around the rubber planting. The main survey is done to take samples of weeds in every age group, every group performed 5 times the sampling is considered to represent the age group. The variables measured were type of weed, SDR, and the coefficient Communities (C).The results showed that the weed dominant in the younger age group (1-5 years): Cyperus Kyllingia, Axonopus compressus, Clibadium Surinames, adolescent age group (6-10 years): Cyperus Kyllingia, Paspalum conjugatum Berg, Calopogonium mucuinoides Desv., Group age youth (11-15 years): Cyperus Kyllingia, Paspalum conjugatum Berg, Chromolaena odorata., adult group (16-20 years): Eleusine indica, Paspalum conjugatum Berg, Chromolaena odorata, then the dominant weeds on the slopes of the West-East direction (BT ) is Calopogonium mucuinoides Desv., Clibadium Surinames, Paspalum conjugatum Berg, and the dominant weed species in the North-South direction of the slope (US) is Calopogonium mucuinoides Desv., Paspalum conjugatum Berg., and Axonopus compressus. Weeds dominant age group and Directions Slope is Cyperus killingia and Eleusine indica (L), Paspalum conjugatum Berg, Axonopus compressus, Clibadium Surinames and Calopogonium mucuinoides Desv.